Implementation of Special Moment Resisting Frame for the Design Structure of a Seven-Story Academic Building in Pontianak - Saputra, Muhammad Akmal; Budi, Gatot Setya; Yusuf, M. (Jurnal Teknik Sipil, 2025)
Education is fundamental to human development, enabling individuals to cultivate logical thinking and continuously evolve, fostering positive behaviors and attitudes. This is especially crucial for the younger generation today. The increasing development and construction of lecture buildings in Pontianak City significantly support education and intellectual growth. Lecture buildings are designed as multi-story structures to address land limitations while accommodating large capacities. The structural design of a seven-story earthquake-resistant lecture building in Pontianak City utilizes a reinforced concrete structure and follows the Structural Concrete Requirements for Buildings and Explanations (SNI 2847:2019) and the Earthquake Resistance Planning Procedures for Building and Non-Building Structures (SNI 1726:2019). The structural system is planned using a Moment Resisting Frame System, considering seismic forces in the design process. Given that the Seven-Storey Lecture Building falls under Seismic Design Category (KDS) D, the appropriate seismic force-resisting system employed is the Special Moment Resisting Frame System (SRPMK) to ensure structural integrity and earthquake resilience.